2023
DOI: 10.1029/2023ms003697
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Machine Learned Mesoscale Eddy Parameterization Into a Numerical Ocean Circulation Model

Cheng Zhang,
Pavel Perezhogin,
Cem Gultekin
et al.

Abstract: We address the question of how to use a machine learned (ML) parameterization in a general circulation model (GCM), and assess its performance both computationally and physically. We take one particular ML parameterization (Guillaumin & Zanna, 2021, https://doi.org/10.1002/essoar.10506419.1) and evaluate the online performance in a different model from which it was previously tested. This parameterization is a deep convolutional network that predicts parameters for a stochastic model of subgrid momentum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The successful use of small neural networks as efficient surrogate models of SMCs proves that we can replicate the behavior of complex models with high fidelity. Increasing the network size will be explored in the future and will likely require using GPUs for implementation in OGCM (Zhang et al, 2023). 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful use of small neural networks as efficient surrogate models of SMCs proves that we can replicate the behavior of complex models with high fidelity. Increasing the network size will be explored in the future and will likely require using GPUs for implementation in OGCM (Zhang et al, 2023). 3.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of small neural networks as efficient surrogate models of SMCs proves that we can replicate the behavior of complex models with high fidelity. Increasing the network size will be explored in the future and will likely require using GPUs for implementation in OGCM (Zhang et al., 2023). The performance of the modified vertical mixing scheme in a coupled model (atmosphere‐ocean‐ice) may not show the same impact on model bias as observed in this forced ocean‐ice model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking to similar studies, Guillaumin and Zanna (2021) found that implementing a fully CNN with 8 convolutional layers as a stochastic parameterization into an idealized shallow water model resulted in a 25% increase in the run time, compared to an unparameterized simulation. C. Zhang et al (2023) also found that the cost of doing inference with this same network as a parameterization in MOM6 was 10 times more expensive than the CPU cost of the simulation itself. Although we effectively have 8 convolutional layers when considering both networks A and B, we can still expect much lower computational overheads given that ours is a deterministic model (i.e., we predict a single output at each grid point for each ΔSICN, rather than a, potentially larger, number of parameters which describe a distribution of values), and that our kernel size for network B is 1 × 1 in each layer.…”
Section: Considerations For Parameterizationmentioning
confidence: 98%
“…Typically this is achieved by training an ML model to learn a functional mapping which characterizes the impact of subgrid processes on resolved scales, by training on high resolution simulations or observational data. Significant effort is currently being afforded to the development of these ML parameterizations in the context of for example, ocean turbulence, with early results (Frezat et al., 2022; Kurz et al., 2023; Ross et al., 2023; Zanna & Bolton, 2020; C. Zhang et al., 2023) highlighting their potential to improve important climate statistics, such as eddy kinetic energy at large scales, over their traditional physics‐based counterparts. Meanwhile, only recently have studies begun to investigate ML‐based subgrid sea ice parameterizations.…”
Section: Introductionmentioning
confidence: 99%